Polyurethane preparation method and polyurethane-based toughened bonding explosive preparation method
Through the preparation method of supramolecular polyurethane, high-density hydrogen bonds are used to form crosslinking points and dynamic reversibility, the problem of insufficient performance of traditional explosive binders is solved, and the performance of bonded explosives with high strength, high toughness and self-healing is achieved.
Patent Information
- Application Number
- CN202411567849.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-05
AI Technical Summary
Traditional explosive binders have limitations in strength, stability and functionality, and it is difficult to meet the high requirements of modern high-performance weapon systems for the detonation performance of explosive charges.
The supramolecular polyurethane preparation method is adopted to form crosslinking points through high-density hydrogen bond interactions, improve the strength and toughness of the binder, and impart the self-healing ability of the material through the dynamic reversibility of hydrogen bonds.
It significantly improves the performance of bonded explosives, provides high strength, high toughness and extraordinary stretchability, extends service life and maintains good bonding properties.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane materials, and particularly relates to a method for preparing polyurethane and a method for preparing toughened bonding explosive based on polyurethane. Background Art
[0002] With the rapid development of modern high-performance weapon systems, the safety of ammunition has become increasingly prominent, and new conventional weapons have put forward higher requirements on the detonation performance of explosive charges. Polymer bonded explosives (PBX), as high-energy composite materials, are widely used in the fields of national defense and national economy, while the performance requirements of binders in the field of explosives are becoming increasingly stringent. Traditional explosive binders have limitations in terms of strength, stability and functionality.
[0003] In this context, polyurethane has attracted much attention due to its excellent comprehensive performance, recyclability and broad application prospects. Polyurethane generated by the reaction of hydroxyl-terminated polyols and diisocyanates has the advantages of strong bonding, good toughness and buffering performance, good weather resistance, strong adjustability, high safety and relatively good environmental protection in terms of explosive binders, making it an ideal choice for explosive binders. At the same time, supramolecular polyurethane constructed through supramolecular interactions has excellent mechanical properties and self-healing properties, providing high-strength and tough bonding for explosives and extending their service life and reliability.
[0004] At present, although the development of supramolecular polyurethanes for explosive binders faces many challenges, their potential application value is huge. Through in-depth research on the preparation methods of supramolecular polyurethanes, it is expected to bring innovative solutions to the field of explosives, improve the performance and safety of explosives, and meet the needs of modern military and industrial fields for high-performance explosives. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a polyurethane preparation method and a polyurethane-based toughened bonded explosive preparation method. Compared with the traditional polymer binder system, the supramolecular polyurethane-based polymer bonded explosive obtained by the preparation method of the present invention has more advantages in strength and toughness, and significantly improves the performance of the bonded explosive.
[0006] In the supramolecular polyurethane network, high-density hydrogen bond interactions form crosslinking points between or within polyurethane molecular chains, increasing the intermolecular forces and thus improving the strength of the adhesive. At the same time, the dynamic process of hydrogen bond breaking and reforming can effectively dissipate energy, giving the adhesive high stretchability and toughness, allowing it to better adapt to the deformation of the bonded object. In addition, the dynamic reversibility of hydrogen bonds gives polyurethane the ability to self-repair, which can self-repair minor damage to the adhesive during use, extend its service life and maintain good bonding performance. Thanks to the dynamic reversible hierarchical hydrogen bonding in the polymer network structure, the prepared supramolecular polyurethane material has high strength, high toughness and extraordinary stretchability.
[0007] The Brazilian tensile test also shows that supramolecular polyurethane-based polymer bonded explosives show great advantages in the field of polymer applications in bonded explosives.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] A method for preparing polyurethane comprises the following steps:
[0010] (1) Place the polyester polyol in a reaction vessel, stir under an oil bath condition of 100-150°C and an inert gas atmosphere, and remove water and dry;
[0011] (2) adding an organic solvent as a reaction solvent into a reaction container and stirring the mixture to obtain a mixed solution;
[0012] (3) After the temperature of the mixed solution is cooled to 60-100° C., diisocyanate is added to the reaction container under an inert gas atmosphere, and then dibutyltin dilaurate is added as a catalyst, and the reaction is carried out in the inert gas atmosphere for 2 h to 5 h to obtain a polyurethane prepolymer;
[0013] (4) adding a diamine chain extender dropwise to the polyurethane prepolymer, and continuing to stir and react for 30 min to 6 h at 40-100 °C in an inert gas atmosphere;
[0014] (5) After the reaction is completed, the solution is poured into a polytetrafluoroethylene mold and vacuum-dried at 60°C to 100°C to remove the residual solvent to obtain a polyurethane film with a thickness of 100 μm to 1000 μm.
[0015] Specifically, a polyurethane preparation method comprises the following steps: first, polyester polyols (molecular weight range: 1000-3000; polyol type: polycarbonate diol / polytetrahydrofuran diol) are selected and mixed into a three-necked flask, stirred for a certain time (60min-150min) under an oil bath condition of 100-150°C and a nitrogen atmosphere, and then dried after dehydration.
[0016] Next, after the temperature of the mixed solution is cooled to 60-100°C, an equivalent amount of diisocyanate (optional type: hexamethylene diisocyanate (HDI) / isophorone diisocyanate (IPDI) / diphenylmethane diisocyanate (MDI) / 4,4'-dicyclohexylmethane diisocyanate (HMDI)) is added, and a certain amount of organic solvent (optional solvent: N,N-dimethylformamide / N,N-dimethylacetamide / dimethyl sulfoxide) is measured, the two are mixed and added dropwise to the reaction bottle, and a certain amount of dibutyltin dilaurate (DBTDL) is added dropwise as a catalyst. The reaction is carried out in a N2 atmosphere for 2h-5h, and the amount of the organic solvent is appropriately adjusted to control the viscosity of the reactants to prevent gelation, thereby obtaining a polyurethane prepolymer.
[0017] After the prepolymer is prepared, a small molecule diamine chain extender (including one or more of polyetheramine, dihydrazine, diaminodicyclohexylmethane, 2-urea-4[H]-pyrimidone-2-amino-2-methyl-1,3-propanediol, and isophthalic acid hydrazide) is slowly added dropwise, and the mixture is stirred for 2 h to 6 h at 40-100 ° C and N2 atmosphere until the reaction is completed.
[0018] After the reaction is completed, the solution is poured into a polytetrafluoroethylene mold and dried at 60°C to 100°C under vacuum for 24h to 72h to remove the residual solvent to obtain a polyurethane film.
[0019] Furthermore, in step (1), the molecular weight of the polyester polyol is in the range of 1000 to 5000; the polyester polyol is polycarbonate diol and / or polytetrahydrofuran diol. For example, in step (1), the molecular weight of the polyester polyol is 1000, 2000, 3000, 4000 or 5000.
[0020] Furthermore, the ratio of the polyester polyol in step (1) to the organic solvent in step (2) is 1:20 to 1:1 g / mL. For example, the ratio of the polyester polyol in step (1) to the organic solvent in step (2) is 1:20 g / mL, 1:15 g / mL, 1:10 g / mL, 1:8 g / mL, 1:6 g / mL, 1:4 g / mL, 1:2 g / mL or 1:1 g / mL.
[0021] Furthermore, the organic solvent in step (2) is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, chloroform and dimethyl sulfoxide.
[0022] Further, in step (3), the mass ratio of the diisocyanate to dibutyltin dilaurate is 1:50-1:10. For example, the mass ratio of the diisocyanate to dibutyltin dilaurate is 1:50, 1:40, 1:30, 1:20 or 1:10. The mass ratio of the diisocyanate to the polyester polyol in step (1) is 1-20:1-100. For example, the mass ratio of the diisocyanate to the polyester polyol in step (1) is 1-20:1, 1-20:20, 1-20:40, 1-20:60, 1-20:80 or 1-20:100.
[0023] Furthermore, in step (4), the mass ratio of the diamine chain extender to the polyester polyol in step (1) is 1-20:1-100. For example, the mass ratio of the diamine chain extender to the polyester polyol in step (1) is 1-20:1, 1-20:20, 1-20:40, 1-20:60, 1-20:80 or 1-20:100.
[0024] Furthermore, in step (5), the thickness of the polyurethane film is 100-1000 μm. For example, in step (5), the thickness of the polyurethane film is 100 μm, 300 μm, 500 μm, 700 μm, 900 μm or 1000 μm.
[0025] The present invention also provides a method for preparing a toughened bonded explosive of polyurethane prepared by any of the above methods, comprising the following steps: preparing a polyurethane film into a dilute solution, adding explosives in a measured proportion, heating to gradually volatilize the solvent, adding an appropriate amount of deionized water to precipitate the supramolecular polyurethane and then coat the surface of the explosive, filtering and drying to obtain a supramolecular polyurethane-based polymer bonded explosive.
[0026] Specifically, the method for preparing the toughened bonded explosive of polyurethane prepared by any of the above methods comprises the following steps:
[0027] (a) crushing the polyurethane film into particles with an average diameter of 1 to 10 mm, and then dissolving the particles in an organic solvent to prepare a solution A;
[0028] (b) placing the explosive in deionized water, stirring, and heating to obtain a uniform dispersion;
[0029] (c) adding the solution A dropwise to the dispersion obtained in step (b), vacuum treating, filtering, washing and heating to gradually volatilize the solvent, drying to precipitate the supramolecular polyurethane and coat the surface of the explosive, filtering and drying to obtain a polyurethane-based toughened bonded explosive.
[0030] Further, in step (a), the concentration of the polyurethane film in solution A is 0.01-1.0 g / mL. For example, in solution A, the concentration of the polyurethane film is 0.01 g / mL, 0.03 g / mL, 0.05 g / mL, 0.07 g / mL, 0.09 g / mL, 0.1 g / mL, 0.3 g / mL, 0.5 g / mL, 0.7 g / mL, 0.9 g / mL or 1.0 g / mL.
[0031] Further, in step (b), the average particle size of the explosive is 50-100 μm; and the mass concentration of the explosive in the dispersion is 0.01-1.0 g / mL. For example, the average particle size of the explosive is 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm; and the mass concentration of the explosive in the dispersion is 0.01 g / mL, 0.03 g / mL, 0.05 g / mL, 0.07 g / mL, 0.09 g / mL, 0.1 g / mL, 0.3 g / mL, 0.5 g / mL, 0.7 g / mL, 0.9 g / mL or 1.0 g / mL.
[0032] Furthermore, in step (c), the volume ratio of solution A to the dispersion is 1-20:10-100. For example, the volume ratio of solution A to the dispersion is 1-20:10, 1-20:30, 1-20:50, 1-20:70, 1-20:90 or 1-20:100.
[0033] Further, in step (c), based on the total mass of the toughened bonded explosive based on polyurethane, the mass percentage of polyurethane in the toughened bonded explosive based on polyurethane is 2-16wt%, and the mass percentage of explosive is 84wt%-98wt%. For example, based on the total mass of the toughened bonded explosive based on polyurethane, the mass percentage of polyurethane in the toughened bonded explosive based on polyurethane is 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, 12wt%, 14wt% or 16wt%, and the mass percentage of explosive is 84wt%, 86wt%, 88wt%, 90wt%, 92wt%, 94wt%, 96wt% or 98wt%.
[0034] The present invention has the following beneficial effects:
[0035] The present invention achieves a significant improvement in the performance of supramolecular polyurethane-based polymer-bonded explosives. Compared with traditional polymer binder systems, it has more advantages in strength and toughness. The Brazilian experiment is used to indirectly investigate and evaluate the tensile properties of explosives. Examples 1-5 show higher Brazilian strain or excellent Brazilian strength, and the mechanical properties significantly exceed those of traditional F2314 adhesives, which has great application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Infrared spectrum of PU-1 at wavelengths of 500~4000 nm
[0037] Figure 2 Infrared spectrum of PU-2 at wavelengths of 500~4000 nm;
[0038] Figure 3 Infrared spectrum of PU-3 at wavelengths of 500~4000 nm;
[0039] Figure 4 Infrared spectrum of PU-4 at wavelengths of 500~4000 nm;
[0040] Figure 5 Infrared spectrum of PU-5 at wavelengths of 500~4000 nm;
[0041] FIG6 is a schematic diagram summarizing stress-strain curves of the embodiment;
[0042] FIG7 is a rheological curve of storage modulus and loss modulus as a function of temperature of Example 1;
[0043] FIG8 is a rheological curve of storage modulus and loss modulus as a function of temperature in Example 2;
[0044] FIG9 is a rheological curve of storage modulus and loss modulus as a function of temperature of Example 3;
[0045] FIG10 is a rheological curve of storage modulus and loss modulus as a function of temperature of Example 4;
[0046] FIG11 is a rheological curve of storage modulus and loss modulus as a function of temperature of Example 5;
[0047] Figure 12 Schematic diagram of the preparation of supramolecular polyurethane-based polymer bonded explosives;
[0048] Fig. 13 Comparison of Brazilian experimental results of supramolecular polyurethane-based polymer bonded explosives. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In order to achieve the above-mentioned purpose, the present invention adopts the following technical solution:
[0050] Embodiment 1:
[0051] (1) First, weigh 10.00 g of PCDL-3000 polycarbonate diol (manufacturer: Guangdong Wengjiang Chemical Reagent Co., Ltd., product number: PB11059, weight average molecular weight is 3000) and place it in a three-necked flask. Heat and stir in an oil bath at 120°C under a nitrogen atmosphere for 2 h, remove water, and dry.
[0052] (2) Add 30 mL of N,N-dimethylformamide as the reaction solvent and stir for 30 minutes to mix evenly.
[0053] (3) After the temperature of the mixed solution was cooled to 80°C, 2.23 g of isophorone diisocyanate and 0.10 g of dibutyltin dilaurate were added to a three-necked flask under a nitrogen environment and reacted for 3 hours to obtain a polyurethane prepolymer.
[0054] (4) After the prepolymer is prepared, 1.15 g of polyetheramine (manufacturer: Jining Hongming Chemical Reagent Co., Ltd., brand: 02, weight average molecular weight is 230, the same as in the following examples) is weighed and dissolved in 20 mL of N,N-dimethylformamide. After mixing evenly, the mixture is slowly added dropwise to a three-necked flask. The mixture is stirred and reacted for 1 h at 50°C under a nitrogen atmosphere.
[0055] (5) After the reaction, the obtained mixture was poured into a polytetrafluoroethylene mold and dried at 80°C under vacuum for 48 hours to completely remove the solvent to obtain a polyurethane film. The film sample was named PU-1, and the average thickness was about 0.5 mm. Figure 1 This is the infrared spectrum of PU-1 at a wavelength of 500~4000 nm.
[0056] Embodiment 2:
[0057] (1) First, weigh 10.00 g of PCDL-3000 polycarbonate diol (manufacturer: Guangdong Wengjiang Chemical Reagent Co., Ltd., product number: PB11059, weight average molecular weight is 3000) and place it in a three-necked flask. Heat and stir in an oil bath at 120°C under a nitrogen atmosphere for 2 h, remove water, and dry.
[0058] (2) Add 30 mL of N,N-dimethylformamide as the reaction solvent and stir for 30 minutes to mix evenly.
[0059] (3) After the temperature of the mixed solution was cooled to 80°C, 2.23 g of isophorone diisocyanate and 0.10 g of dibutyltin dilaurate were added to a three-necked flask under a nitrogen environment and reacted for 3 hours to obtain a polyurethane prepolymer.
[0060] (4) After the prepolymer is prepared, weigh 0.485 g of p-dibenzoic acid dihydrazide and dissolve it in 10 mL of dimethyl sulfoxide. After mixing evenly, slowly add it dropwise to the three-necked flask. Continue stirring and reacting at 50°C under nitrogen atmosphere for 1 h.
[0061] (5) Weigh 0.575 g of polyetheramine and dissolve it in 10 mL of N,N-dimethylformamide. After mixing evenly, slowly add the mixture dropwise to the three-necked flask. Continue stirring and reacting at 50°C under nitrogen atmosphere for 1 h.
[0062] (6) After the reaction, the obtained mixture was poured into a polytetrafluoroethylene mold and dried at 80°C under vacuum for 48 hours to completely remove the solvent to obtain a polyurethane film. The film sample was named PU-2, and the average thickness was about 0.5 mm. Figure 2 This is the infrared spectrum of PU-2 at a wavelength of 500~4000 nm.
[0063] Embodiment 3:
[0064] (1) First, weigh 10.00 g of PCDL-3000 polycarbonate diol (manufacturer: Guangdong Wengjiang Chemical Reagent Co., Ltd., product number: PB11059, weight average molecular weight is 3000) and place it in a three-necked flask. Heat and stir in an oil bath at 120°C under a nitrogen atmosphere for 2 h, remove water, and dry.
[0065] (2) Add 30 mL of N,N-dimethylformamide as the reaction solvent and stir for 30 minutes to mix evenly.
[0066] (3) After the temperature of the mixed solution was cooled to 80°C, 2.23 g of isophorone diisocyanate and 0.10 g of dibutyltin dilaurate were added to a three-necked flask under a nitrogen environment and reacted for 3 hours to obtain a polyurethane prepolymer.
[0067] (4) After the prepolymer is prepared, weigh 0.526 g of diaminodicyclohexylmethane and dissolve it in 10 mL of N,N-dimethylformamide. After mixing evenly, slowly add it dropwise to the three-necked flask and continue stirring and reacting at 80°C under nitrogen atmosphere for 1 h.
[0068] (5) Weigh 0.995 g of 2-urea-4[H]-pyrimidinone-2-amino-2-methyl-1,3-propanediol and dissolve it in 10 mL of N,N-dimethylformamide. After mixing evenly, slowly add the mixture dropwise to the three-necked flask and continue stirring the reaction at 80°C under nitrogen atmosphere for 3 h.
[0069] (6) After the reaction, the obtained mixture was poured into a polytetrafluoroethylene mold and dried at 80°C under vacuum for 48 hours to completely remove the solvent to obtain a polyurethane film. The film sample was named PU-3, and the average thickness was about 0.5 mm. Figure 3 This is the infrared spectrum of PU-3 at a wavelength of 500~4000 nm.
[0070] Embodiment 4:
[0071] (1) First, weigh 10.00 g of PCDL-2000 polycarbonate diol (manufacturer: Jining Liduo Chemical Co., Ltd., product number: LD1068, weight average molecular weight is 2000) and place it in a three-necked flask. Heat and stir in an oil bath at 120°C under a nitrogen atmosphere for 2 h, remove water, and dry.
[0072] (2) Add 30 mL of N,N-dimethylformamide as the reaction solvent and stir for 30 minutes to mix evenly.
[0073] (3) After the temperature of the mixed solution was cooled to 80°C, 2.23 g of isophorone diisocyanate and 0.10 g of dibutyltin dilaurate were added to a three-necked flask under a nitrogen environment and reacted for 3 hours to obtain a polyurethane prepolymer.
[0074] (4) After the prepolymer is prepared, weigh 1.05 g of diaminodicyclohexylmethane and dissolve it in 20 mL of N,N-dimethylformamide. After mixing evenly, slowly add it dropwise to the three-necked flask. Continue stirring and reacting at 80°C under nitrogen atmosphere for 1 h.
[0075] (5) After the reaction, the obtained mixture was poured into a polytetrafluoroethylene mold and dried at 80°C under vacuum for 48 hours to completely remove the solvent to obtain a polyurethane film. The film sample was named PU-4, and the average thickness was about 0.5 mm. Figure 4 This is the infrared spectrum of PU-4 at a wavelength of 500~4000 nm.
[0076] Embodiment 5:
[0077] (1) First, weigh 10.00 g of PCDL-2000 polycarbonate diol (manufacturer: Jining Liduo Chemical Co., Ltd., product number: LD1068, weight average molecular weight is 2000) and place it in a three-necked flask. Heat and stir in an oil bath at 120°C under a nitrogen atmosphere for 2 h, remove water, and dry.
[0078] (2) Add 30 mL of N,N-dimethylformamide as the reaction solvent and stir for 30 minutes to mix evenly.
[0079] (3) After the temperature of the mixed solution was cooled to 80°C, 2.23 g of isophorone diisocyanate and 0.10 g of dibutyltin dilaurate were added to a three-necked flask under a nitrogen environment and reacted for 3 hours to obtain a polyurethane prepolymer.
[0080] (4) After the prepolymer is prepared, weigh 0.776 g of isophthalic acid hydrazide and dissolve it in 20 mL of dimethyl sulfoxide. After mixing evenly, slowly add it dropwise to the three-necked flask. Continue stirring and reacting at 80°C under nitrogen atmosphere for 1 h.
[0081] (5) Weigh 0.23 g of polyetheramine and dissolve it in 15 mL of N,N-dimethylformamide. After mixing evenly, slowly add the mixture dropwise to the three-necked flask. Continue stirring and reacting at 50°C under nitrogen atmosphere for 3 h.
[0082] (6) After the reaction, the obtained mixture was poured into a polytetrafluoroethylene mold and dried at 80°C under vacuum for 48 hours to completely remove the solvent to obtain a polyurethane film. The film sample was named PU-5, and the average thickness was about 0.5 mm. Figure 5 This is the infrared spectrum of PU-5 at a wavelength of 500~4000 nm.
[0083] Test results:
[0084] 1. Mechanical properties of polyurethane adhesive
[0085] In order to effectively evaluate the mechanical properties of the prepared polyurethane materials, stress-strain curve tests were performed on all samples prepared in Examples 1 to 5. The results are shown in Figure 6 are shown and summarized in Table 1.
[0086] Summary of stress-strain curves of the examples:
[0087] Test standard: GB / T 1040-2006;
[0088] Test speed (i.e. tensile rate): 100 mm / min, test environment: 25°C.
[0089] The mechanical properties of the samples prepared in Examples 1 to 5 at the same tensile rate are summarized as follows:
[0090] Toughness of a material: the area under the stress-strain curve.
[0091] That is, the energy absorbed by a unit volume of material before fracture occurs.
[0092] Table 1 Elongation at break, ultimate tensile strength and toughness of samples prepared in Examples 1 to 5
[0093]
[0094] Depend on Figure 6 As shown in the results of Table 1, all the samples of the embodiments showed ultra-high stretchability, outstanding tensile strength and excellent toughness. Compared with traditional polymer networks, the polyurethane network structure obtained by the preparation method proposed in the present invention contains abundant supramolecular interactions (i.e. strong and weak hydrogen bonds). High-density hydrogen bond interactions can form cross-linking points between polyurethane molecular chains or within molecular chains, increase the intermolecular forces, and thus improve the strength of polyurethane. When polyurethane is subjected to external forces, hydrogen bonds can break and reform. This dynamic process can effectively dissipate energy, giving the material high stretchability and toughness. In addition, the dynamic reversibility of hydrogen bonds enables polyurethane to have the ability to self-repair, and can self-repair minor damage to the adhesive during use, thereby extending the service life of the adhesive and maintaining bonding performance.
[0095] Therefore, through reasonable molecular design and regulation of the distribution of soft and hard segments, the polyurethane material prepared by the present invention exhibits extraordinary mechanical properties and is expected to be used as a high-performance explosive binder.
[0096] 2. Rheological properties analysis
[0097] Rheological properties can affect the interface contact and interaction between the adhesive and the bonded materials. For example, at the right temperature, an adhesive with appropriate viscosity and fluidity can better wet the surface of the bonded materials, forming stronger mechanical and chemical bonds, thereby improving bond strength and durability.
[0098] The rheological properties of the samples prepared in Examples 1 to 5 were tested:
[0099] The test was conducted using a rheometer (Haake Mars40, Germany);
[0100] Test atmosphere: nitrogen, test temperature range: 20℃ to 160℃, oscillation mode.
[0101] Storage modulus and loss modulus of the samples prepared in Examples 1 to 5 vary with temperature:
[0102] Depend on Figures 7 to 11 It can be seen that all samples have an intersection of loss modulus and storage modulus in the range of 90~110℃, and the temperature corresponding to this intersection is identified as the glass transition temperature (Tg) of the material. Below Tg, the material mainly behaves in a glassy state, the movement of the molecular chain is greatly restricted, the storage modulus is high, and the loss modulus is relatively low. Above Tg, the material gradually transforms into a highly elastic state, and the molecular chain can move to a larger extent.
[0103] In the present invention, the preparation conditions of the bonded explosive are a temperature of 120° C. and a pressure of 110 KN. Since the material gradually changes to a highly elastic state above Tg, when the preparation temperature is 120° C., the material is in a highly elastic state, and the molecular chain can move to a certain extent, so that during the preparation process, the polyurethane can exert fluidity, better fill the gaps between the explosive particles, and ensure the uniformity and density of the explosive column.
[0104] 3. Preparation method of supramolecular polyurethane-based polymer bonded explosive
[0105] Fig.12 Schematic diagram of the preparation process of supramolecular polyurethane-based polymer bonded explosives. Fig.13 The Brazilian strength and strain results of supramolecular polyurethane-based polymer bonded explosives are compared. The polyurethane prepared in Examples 1-5 is used as a binder, and the specific method for preparing supramolecular polyurethane-based polymer bonded explosives based on the binders in Examples 1-5 is as follows.
[0106] Test Example 1:
[0107] Preparation method of adhesive supramolecular polyurethane-based polymer bonded explosive based on Example 1:
[0108] (1) The polyurethane film of Example 1 was crushed into a sample with an average particle size of about 3 mm. 0.8 g of the sample was dissolved in 10 ml of chloroform to obtain a binder solution.
[0109] (2) 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) (9.2 g) with an average particle size of 80 μm is added to deionized water (100 ml), and the mixture is mechanically stirred (stirring rate: 600 rpm). After being evenly dispersed and heated to 45° C., the binder solution obtained in step (1) is added dropwise (the final binder accounts for 8% by weight of the energetic composite). After vacuum treatment, filtration, washing, and drying (drying temperature and time: 80° C., 24 h), a polymer-bonded explosive (i.e., an energetic composite) based on supramolecular polyurethane is obtained.
[0110] (3) The bonded explosive obtained in step (2) is pressed at 120°C and 110KN pressure to form a 20mmX6mm (20mm is the diameter and 6mm is the height, the same below) explosive column, the Brazilian fracture strength is 4.4MPa, and the Brazilian fracture strain is 1.4%. Under the same preparation conditions, compared with the use of traditional fluoropolymer binder (the traditional fluoropolymer binder is F2314 (F2314 is copolymerized by 20% (mol) vinylidene fluoride and 80% (mol) trifluoroethylene, Zhonghao Chenguang Chemical Research Institute Co., Ltd., the same below), the Brazilian fracture strength and strain are 5.14MPa and 0.13% respectively), the Brazilian fracture strain of the obtained polymer bonded explosive is greatly improved.
[0111] Test Example 2:
[0112] Preparation method of adhesive supramolecular polyurethane-based polymer bonded explosive based on Example 2:
[0113] (1) The polyurethane film of Example 2 was crushed into a sample with an average particle size of about 3 mm. 0.8 g of the sample was dissolved in 10 ml of chloroform to obtain a binder solution.
[0114] (2) 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) (9.2 g) with an average particle size of 80 μm was added to deionized water (100 ml), and the mixture was mechanically stirred (stirring rate: 600 rpm). After being evenly dispersed and heated to 45° C., the binder solution obtained in step (1) was added dropwise (the final binder accounted for 8% by weight of the energetic composite). After vacuum treatment, filtration, washing, and drying (drying temperature and time: 80° C., 24 h), a polymer-bonded explosive (i.e., an energetic composite) based on supramolecular polyurethane was obtained.
[0115] (3) The bonded explosive obtained in step (2) was pressed at 120°C and 110KN pressure to form a 20mmX6mm column, with a Brazilian fracture strength of 5.67MPa and a Brazilian fracture strain of 0.974%. Under the same preparation conditions, compared with the use of traditional fluoropolymer binder (fluoropolymer binder is F2314, Brazilian fracture strength and strain are 5.14MPa and 0.13% respectively), the Brazilian fracture strength and strain of the obtained polymer bonded explosive are significantly improved.
[0116] Test Example 3:
[0117] Preparation method of adhesive supramolecular polyurethane-based polymer bonded explosive based on Example 3:
[0118] (1) The polyurethane film of Example 3 was crushed into a sample with an average particle size of about 3 mm. 0.8 g of the sample was dissolved in 10 ml of chloroform to obtain a binder solution.
[0119] (2) 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) (9.2 g) with an average particle size of 80 μm is added to deionized water (100 ml), and the mixture is mechanically stirred (stirring rate: 600 rpm). After being evenly dispersed and heated to 45° C., the binder solution obtained in step (1) is added dropwise (the final binder accounts for 8% by weight of the energetic composite). The mixture is subjected to vacuum treatment, suction filtration, washing, and drying (drying temperature and time: 80° C., 24 h) to obtain a polymer-bonded explosive (i.e., an energetic composite) based on supramolecular polyurethane.
[0120] (3) The bonded explosive obtained in step (2) was pressed at 120°C and 110KN pressure to form a 20mmX6mm column, with a Brazilian fracture strength of 5.5MPa and a Brazilian fracture strain of 0.778%. Under the same preparation conditions, compared with the use of traditional fluoropolymer binder (fluoropolymer binder is F2314, Brazilian fracture strength and strain are 5.14MPa and 0.13% respectively), the Brazilian fracture strength and strain of the obtained polymer bonded explosive are significantly improved.
[0121] Test example 4:
[0122] Preparation method of adhesive supramolecular polyurethane-based polymer bonded explosive based on Example 4:
[0123] (1) The polyurethane film of Example 4 was crushed into a sample with an average particle size of about 3 mm. 0.8 g of the sample was dissolved in 10 ml of chloroform to obtain a binder solution.
[0124] (2) 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) (9.2 g) with an average particle size of 80 μm is added to deionized water (100 ml), and the mixture is mechanically stirred (stirring rate: 600 rpm). After being evenly dispersed and heated to 45° C., the binder solution obtained in step (1) is added dropwise (the final binder accounts for 8% by weight of the energetic composite). The mixture is subjected to vacuum treatment, suction filtration, washing, and drying (drying temperature and time: 80° C., 24 h) to obtain a polymer-bonded explosive (i.e., an energetic composite) based on supramolecular polyurethane.
[0125] (3) The bonded explosive obtained in step (2) was pressed at 120°C and 110KN pressure to form a 20mmX6mm column, with a Brazilian fracture strength of 7.55MPa and a Brazilian fracture strain of 0.537%. Under the same preparation conditions, compared with the use of traditional fluoropolymer binder (polymer F2314, Brazilian fracture strength and strain are 5.14MPa and 0.13% respectively), the Brazilian fracture strength and strain of the obtained polymer bonded explosive are significantly improved.
[0126] Test Example 5:
[0127] Preparation method of adhesive supramolecular polyurethane-based polymer bonded explosive based on Example 5:
[0128] (1) The polyurethane film of Example 5 was crushed into a sample with an average particle size of about 3 mm. 0.8 g of the sample was dissolved in 10 ml of chloroform to obtain a binder solution.
[0129] (2) 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) (9.2 g) with an average particle size of 80 μm was added to deionized water (100 ml), and the mixture was mechanically stirred (stirring rate: 600 rpm). After being evenly dispersed and heated to 45° C., the binder solution obtained in step (1) was added dropwise (the final binder accounted for 8% by weight of the energetic composite). After vacuum treatment, filtration, washing, and drying (drying temperature and time: 80° C., 24 h), a polymer-bonded explosive (i.e., an energetic composite) based on supramolecular polyurethane was obtained.
[0130] (3) The bonded explosive obtained in step (2) was pressed at 120°C and 110KN pressure to form a 20mmX6mm column, with a Brazilian fracture strength of 8.25MPa and a Brazilian fracture strain of 0.639%. Under the same preparation conditions, compared with the use of traditional fluoropolymer binder (fluoropolymer binder is F2314, Brazilian fracture strength and strain are 5.14MPa and 0.13% respectively), the Brazilian fracture strength and strain of the obtained polymer bonded explosive are significantly improved.
[0131] The tensile properties of explosives are usually indirectly investigated and evaluated using the Brazilian test. Test cases 1 to 5 all showed high Brazilian strain or excellent Brazilian strength. Compared with the traditional F2314 adhesive, its mechanical properties have been significantly improved, showing great application potential.
[0132] Comparative Example 1 (traditional F2314 adhesive) and Comparative Example 2 were used as comparative examples of Example 1, and the superiority and advancement of the method of the present invention were demonstrated by evaluating the mechanical properties of different polyurethane materials and the Brazilian strength and strain when used as explosive binders.
[0133] The Brazilian experimental results of Comparative Examples 1 and 2 are as follows:
[0134] Table 2 Brazilian strength and Brazilian strain of comparative example 1 and comparative example 2
[0135]
[0136] By comparison, it is found that the Brazilian strength and Brazilian strain of Comparative Examples 1 and 2 are much lower than the results of Test Examples 1 to 5, and they are not advantageous for use as explosive binders.
[0137] Taking the control test as a comparative example, if the reaction temperature is 20~50℃, we can provide the test plan corresponding to the reaction temperature outside the range of 20~50℃
[0138] Preparation method of comparative example:
[0139] 1. Comparative Example 1:
[0140] Traditional F2314 binder, traditional F2314 is copolymerized by 20 mol% vinylidene fluoride and 80 mol% trifluoroethylene, and is produced by Zhonghao Chenguang Chemical Research Institute Co., Ltd.
[0141] (1) The conventional F2314 binder was crushed into a sample with an average particle size of about 3 mm. 0.8 g of the sample was dissolved in 10 ml of chloroform to obtain a binder solution.
[0142] (2) 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) (9.2 g) with an average particle size of 80 μm was added to deionized water (100 ml), and the mixture was mechanically stirred (stirring rate: 600 rpm). After being evenly dispersed and heated to 45° C., the binder solution obtained in step (1) was added dropwise (the final binder accounted for 8% by weight of the energetic composite material). After vacuum treatment, filtration, washing, and drying (drying temperature and time: 80° C., 24 h), a bonded explosive (i.e., an energetic composite material) based on a conventional F2314 binder was obtained.
[0143] (3) The bonded explosive obtained in step (2) was pressed into a 20 mm x 6 mm column at 120° C. and 110 kN pressure, and the Brazilian fracture strength and strain were 5.14 MPa and 0.13%, respectively.
[0144] 2. Comparative Example 2:
[0145] (1) First, weigh 10.00 g of PTMG-2000 polytetrahydrofuran diol (manufacturer and brand: Jining Hongming Chemical Reagent Co., Ltd., PTMEG2000) and place it in a three-necked flask. Heat and stir in an oil bath at 120°C under a nitrogen atmosphere for 2 h, remove water, and dry.
[0146] (2) Add 30 mL of N,N-dimethylformamide as the reaction solvent and stir for 30 minutes to ensure uniform mixing.
[0147] (3) After the temperature of the mixed solution was cooled to 80°C, 2.23 g of isophorone diisocyanate and 0.10 g of dibutyltin dilaurate were added to a three-necked flask under a nitrogen environment and reacted for 3 hours to obtain a polyurethane prepolymer.
[0148] (4) After the prepolymer is prepared, weigh 1.15 g of polyetheramine and dissolve it in 20 mL of N,N-dimethylformamide. After mixing evenly, slowly add it dropwise to the three-necked flask. The reaction time is about 1 h.
[0149] (5) After the reaction, the obtained mixed solution was poured into a polytetrafluoroethylene mold, and vacuum-dried at 80°C for 48 hours to completely remove the solvent to obtain a film sample, which was used as an adhesive. The film sample was named the adhesive of Comparative Example 2, and the average thickness of the film was about 0.5 mm.
[0150] Explosive preparation method based on the binder of Comparative Example 2:
[0151] (1) The film of Comparative Example 2 was crushed into a sample with an average particle size of about 3 mm. 0.8 g of the sample was dissolved in 10 ml of chloroform to obtain a dispersion.
[0152] (2) 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) (9.2 g) with an average particle size of 80 μm was added to deionized water (100 ml), and the mixture was mechanically stirred (stirring rate: 600 rpm) until uniformly dispersed and heated to 45° C., and then the dispersion obtained in step (1) was added dropwise (the final binder accounted for 8% by weight of the energetic composite), and vacuum treated, filtered, washed, and dried (drying temperature and time: 80° C., 24 h) to obtain a polymer-bonded explosive (i.e., an energetic composite) based on supramolecular polyurethane.
[0153] (3) The bonded explosive obtained in step (2) is pressed at 120° C. and 110 kN pressure to form a 20 mm×6 mm column, the Brazilian fracture strength of which is 4.58 MPa and the Brazilian fracture strain of which is 0.49%.
Claims
1. A use of polyurethane as a binder for toughening bonded explosives, characterized in that: The preparation method of the polyurethane comprises the following steps: (1) Place the polyester polyol in a reaction vessel, stir under an oil bath condition of 100-150°C and an inert gas atmosphere, and remove water and dry; (2) adding an organic solvent as a reaction solvent into a reaction container and stirring the mixture to obtain a mixed solution; (3) After the temperature of the mixed solution is cooled to 60-100° C., diisocyanate is added to the reaction container under an inert gas atmosphere, and then dibutyltin dilaurate is added as a catalyst, and the reaction is carried out in the inert gas atmosphere for 2 h to 5 h to obtain a polyurethane prepolymer; (4) adding a diamine chain extender dropwise to the polyurethane prepolymer, and continuing to stir and react for 30 min to 6 h at 40-100 °C in an inert gas atmosphere; (5) After the reaction is completed, the solution is poured into a polytetrafluoroethylene mold, and vacuum-dried at 60°C to 100°C to remove the residual solvent to obtain a polyurethane film; In step (1), the molecular weight of the polyester polyol is 1000-5000; the polyester polyol is polycarbonate diol; In step (3), the diisocyanate is one, two, three or four of hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate and 4,4'-dicyclohexylmethane diisocyanate; the mass ratio of the diisocyanate to the polyester polyol in step (1) is 1-20:1-80; In step (4), the diamine chain extender is selected from one, two, three, four or five of polyetheramine, p-dibenzoic acid dihydrazine, diaminodicyclohexylmethane, 2-urea-4[H]-pyrimidone-2-amino-2-methyl-1,3-propanediol and isophthalic acid hydrazide; the mass ratio of the diamine chain extender to the polyester polyol in step (1) is 1-20:1-20.
2. The use according to claim 1, characterized in that The ratio of the polyester polyol in step (1) to the organic solvent in step (2) is 1:20-1:1 g / mL; the organic solvent in step (2) is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, chloroform and dimethyl sulfoxide.
3. The use according to claim 1, characterized in that In step (3), the mass ratio of the diisocyanate to dibutyltin dilaurate is 1:50 to 1:10; and the inert gas is argon or nitrogen.
4. The use according to claim 1, characterized in that In step (5), the thickness of the polyurethane film is 100-1000 μm.
5. The use according to claim 1, characterized in that: The use comprises the following steps: (a) crushing the polyurethane film into particles with an average particle size of 1 to 10 mm, and then dissolving the particles in an organic solvent to prepare a solution A; (b) placing the explosive in deionized water, stirring, and heating to obtain a uniform dispersion; (c) adding the solution A dropwise to the dispersion obtained in step (b), vacuum treating, filtering, washing and heating to gradually volatilize the solvent, drying to precipitate the supramolecular polyurethane and coat the surface of the explosive, filtering and drying to obtain a polyurethane-based toughened bonded explosive.
6. The use according to claim 5, characterized in that In step (a), in solution A, the concentration of the polyurethane film is 0.01-1.0 g / mL.
7. The use according to claim 5, characterized in that In step (b), the average particle size of the explosive is 50-100 μm; and the mass concentration of the explosive in the dispersion is 0.01-1.0 g / mL.
8. The use according to claim 5, characterized in that In step (c), the volume ratio of solution A to the dispersion is 1-20:10-100.
Citation Information
Patent Citations
Damage self-healing polymer-based composite explosive and preparation method thereof
CN110172010A
Polyurethane material with woven cross-linked structure and preparation method thereof
CN117843912A